A numerical method to price exotic path-dependent options on an underlying described by the Heston stochastic volatility model - Ballestra, Luca Vincenzo; Pacelli, Graziella; Zirilli, Francesco (Journal of Banking & Finance, 2007)
We consider the problem of pricing European exotic path-dependent derivatives on an underlying described by the Heston stochastic volatility model. Lipton has found a closed form integral representation of the joint transition probability density function of underlying price and variance in the Heston model. We give a convenient numerical approximation of this formula and we use the obtained approximated transition probability density function to price discrete path-dependent options as discounted expectations. The expected value of the payoff is calculated evaluating an integral with the Monte Carlo method using a variance reduction technique based on a suitable approximation of the transition probability density function of the Heston model. As a test case, we evaluate the price of a discrete arithmetic average Asian option, when the average over n=12 prices is considered, that is when the integral to evaluate is a 2n=24 dimensional integral. We show that the method proposed is computationally efficient and gives accurate results.